2018
DOI: 10.3329/pa.v29i2.38293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different irrigation levels on the performance of wheat

Abstract: An experiment was conducted at the research field of the Department of Agricultural Botany, Patuakhali Science and Technology University, Patuakhali under the Agro-ecological zone-13 (AEZ-13) during the period from November 2012 to February 2013. The aim of the study was to identify the most effective irrigation level for obtaining the better growth and higher yield performance of BARI Gom-25 that are suitable to cultivate under  coastal region of Patuakhali, Bangladesh. So, the present study was consists of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The wheat properties can be affected by the various factors such as the type of soil, type of irrigation, and climatic variations. Earlier published research states that the height of the plant can be significantly increased by providing three irrigations at 25, 40, and 55 DAS [34]. In addition, there is a 40% loss in wheat crop yield due to lack of nutrient scarcity and presence of metal content in the soil [35,36].…”
Section: Characterization Of Physical Propertiesmentioning
confidence: 99%
“…The wheat properties can be affected by the various factors such as the type of soil, type of irrigation, and climatic variations. Earlier published research states that the height of the plant can be significantly increased by providing three irrigations at 25, 40, and 55 DAS [34]. In addition, there is a 40% loss in wheat crop yield due to lack of nutrient scarcity and presence of metal content in the soil [35,36].…”
Section: Characterization Of Physical Propertiesmentioning
confidence: 99%
“…Shirazi et al (2014) [15] observed that plant height was gradually increased with increasing number of irrigations. Islam et al (2018) [16] and Rummana et al (2018) [17] also observed similar results. Patel et al (1992) [18] explained that 12 cm depth of irrigation significantly increased the plant height compared with 6 cm irrigation.…”
Section: Effect Of Irrigation Regimes On Yield Characters and Yieldmentioning
confidence: 56%
“…While, Leghari et al (2017) reported irrigation treatments had significantly affected plant height. Moreover, Islam et al (2018) reported that wheat yield increased with increasing irrigation treatments.…”
Section: Analysis Of Variancementioning
confidence: 99%